Mitigation methods for Terebrasabella heterouncinata, a problematic sabellid polychaete, populations within an abalone (Haliotis midae) production system - Henderson, Ray Arthur (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Animal Sciences. Aquaculture))--University of Stellenbosch, 2006.